Efficacy of mFOLFOX6 plus bevacizumab regimen in advanced colorectal cancer after deep hyperthermia: a single-center retrospective study - Han, Guohu; Cui, Lihua; Sun, Changchun; Yu, Lijiang; Liu, Shenzha (Frontiers in Oncology, 2023)
Background: This study aimed to explore the clinical efficacy and safety of a modified FOLFOX6 (oxaliplatin + leucovorin + 5-fluorouracil) plus bevacizumab regimen after deep hyperthermia in advanced colorectal cancer. Methods: A total of 80 colorectal cancer patients treated at our hospital were selected as research subjects. According to the random number table method, patients were divided into a control group (mFOLFOX6 plus bevacizumab) and a combination group (mFOLFOX6 plus bevacizumab after deep hyperthermia treatment), with 40 patients in each group. After six cycles of treatment, the objective response rate (ORR), disease control rate (DCR), levels of serum tumor markers carcinoembryonic antigen (CEA), vascular epidermal growth factor (VEGF), Karnofsky performance status (KPS) scores, and the occurrence of adverse events were compared between the two groups. Results: After six cycles of treatment, the ORR in the combination group was higher than that in the control group, but the difference was not statistically significant (P>0.05). The DCR in the combination group was significantly higher than that in the control group (P<0.05). The serum CEA levels in the control and combination groups after treatment were significantly lower than those before treatment, and the serum CEA and VEGF levels in the combination group were significantly lower than those in the control group (all P<0.001). The KPS scores in both groups after treatment were higher than those before treatment, and the KPS scores in the combination group after treatment were significantly higher than those in the control group (all P<0.001). The incidence of fatigue and pain in the combination group was significantly lower than that in the control group (P<0.05). Conclusion: mFOLFOX6 plus bevacizumab after deep hyperthermia is effective in advanced colorectal cancer 2 patients, which can effectively improve their quality of life, and the adverse events are controllable and tolerable. A randomized or prospective trial will be required to further prove these data and explore its potentiality, especially if compared to conventional treatment.